What can we learn from severity index on flight data monitoring? analysis of safety resilience in flight operations during COVID-19 disruptions - Li, Wen-Chin; Nichanian, Arthur; Lin, John; Braithwaite, Graham (Taylor & Francis, 2024)
The unexpected spread of the pandemic raised concerns regarding pilots’ skill decay resulting from the significant drops in the frequency of flights by about 70%. This research retrieved 4761 Flight Data Monitoring (FDM) occurrences based on the FDM programme containing 123,140 flights operated by an international airline between June 2019 and May 2021. The FDM severity index was analysed by event category, aircraft type, and flight phase. The results demonstrate an increase in severity score from the pre-pandemic level to the pandemic onset on events that occurred on different flight phases. This trend is not present in the third stage, which indicates that pilots and the safety management system of the airline demonstrated resilience to cope with the flight disruptions during the pandemic. Through the analysis of event severity, FDM enables safety managers to recommend measures to increase safety resilience and self-monitoring capabilities of both operators and regulators.
Keywords: Flight data monitoring; risk assessment; safety resilience; severity index; skill decay